Influence of ultrasonication energy on reinforcing-roles of CNTs to strengthen ITZ and corresponding anti-permeability properties of concrete. (11th October 2021) - Gao, Yuan; Jing, Hongwen; Zhao, Zhenlong; Shi, Xinshuai; Li, Luan
Highlights: Suitable UE would balance the dispersion and tube length of CNTs in suspension. CNTs reduce the ITZ width and abrasion crack width in concrete. The reinforced ITZ would enhance the anti-permeability properties of concrete. CNTs promote the nucleation effects and pore refining effects in concrete. Abstract: Concrete is the most common material used extensively in fundamental construction and engineering. The interfacial transition zone (ITZ), as the region of the cementitious pastes around the aggregate particles, is the weakest area and always limits the performance and application of the concrete. In this study, we used carbon nanotubes (CNTs) as nano-additives to strengthen the ITZ characteristics in concrete and the corresponding anti-permeability reinforcement under different ultrasonication energy (UE). The results prove that balancing the separating and shearing forces during the ultrasonication processes is crucial to ensure the dispersion and suitable particle size of CNTs in their further application. It is found that ultrasonication energy of between 225 J/mL and 338 J/mL can simultaneously ensure the degree of dispersion and the tube-length of CNTs in the suspension, and optimize the ITZ width and abrasion crack width in the ITZ in concrete to 30%–40.2%. The relationship between the ITZ characteristics and UE can be described using a quadratic function. Both the ITZ width and abrasion crack width in the ITZ have a linear correlation with permeability-related parameters in the concrete. After mixing CNTs into concrete specimens, the corresponding anti-permeability properties increased by more than 43% under 270–338 J/mL UE. Scanning electron microscopy observation further reveals that CNTs not only have a nucleating role in generating a higher hydration reaction but also form net-like distributions in the hardened concrete to reinforce the microstructure of the ITZ. However, both insufficient and excess UE will inhibit the superior reinforcing ability of CNTs.